2003
DOI: 10.1055/s-2003-43325
|View full text |Cite
|
Sign up to set email alerts
|

Surgery of Glomus Jugulare Tumors

Abstract: The treatment of choice for glomus jugulare tumors is still controversial. High rates of morbidity, incomplete resection, and the aggressive behavior of these tumors are the main arguments for advocates of primary radiotherapy. However, constant refinements in skull base techniques have made complete resection of these lesions a realistic goal. The high probability of achieving local control of these tumors by surgery has convinced us to support this option strongly. Between 1993 and 2000 we diagnosed 52 glomu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 17 publications
(18 reference statements)
1
32
0
Order By: Relevance
“…As a consequence, the VA is often thought to be of significance only as a feeding vessel via the PICA. In the last 20 years, three cases of direct VA involvement by tumor [Patel et al, 1994;Gardner et al, 1997;Pareschi et al, 2003] have been reported, and this is further supported by the data from our 8 cases.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…As a consequence, the VA is often thought to be of significance only as a feeding vessel via the PICA. In the last 20 years, three cases of direct VA involvement by tumor [Patel et al, 1994;Gardner et al, 1997;Pareschi et al, 2003] have been reported, and this is further supported by the data from our 8 cases.…”
Section: Discussionsupporting
confidence: 89%
“…Inclusion criteria comprised cases describing VA involvement by TJP. There were 3 cases in the English literature that met our inclusion criteria [Patel et al, 1994;Gardner et al, 1997;Pareschi et al, 2003]. Including our 8 cases, a total of 11 cases are summarized in table 3 .…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Advanced or skull base-located tumours are associated with the highest rate of complications and functional disability (with a low response to rehabilitation measures in the elderly). In such tumours, surgery is less effective and more likely to inflict serious damage (Moe et al 1999, Pareschi et al 2003. However, many complications are not permanent or do not significantly affect long-term function significantly (Briner et al 1999).…”
Section: Choice Of Therapymentioning
confidence: 99%